Covid-19: Titik Kisar dan Potret Pendidikan - Nirwansyah Nirwansyah (SALAM: Jurnal Sosial dan Budaya Syar-i, 2020)
The outbreak has historically been a problem that has claimed many victims. In the 21st century, humanity has been shocked by the emergence of three epidemics in the last two decades. The latest outbreak was found in Wuhan, China at the end of 2019 which is called the Novel Coronavirus 2019 or Corona Virus Desease 2019 (Covid-19). The World Health Organization (WHO) has declared the status of Covid-19 as a global pandemic, which in a relatively short time has spread to various countries. Covid-19 has impacted various lines of life such as economy, socio-culture, politics, psychology, education, and so on. The aim of this study is to provide an overview of the implications of the pandemic on education. This study uses a qualitative research method with a library approach sourced from books, journals or scientific papers, articles, and other digital literature. This study describes how Covid-19 can affect and restructure education both in various countries in the world, including Indonesia. The results show that there are three trends that have emerged in the world of global education in the midst of a pandemic and there are four ways that Covid-19 can change the way of educating future generations. So, it is time for the world of education to get out of the status quo and improve towards a futuristic education (education 4.0).Keywords: Corona, Education, Education 4.0 AbstrakSecara historis wabah telah menjadi masalah yang banyak memakan korban. Pada abad ke-21 ini umat manusia dikagetkan dengan munculnya tiga wabah dalam dua dekade terkahir. Wabah terbaru ditemukan di Wuhan, China pada akhir 2019 yang disebut dengan Novel Coronavirus 2019 atau Corona Virus Desease 2019 (Covid-19). Organisasi Kesehatan Dunia (WHO) menetapkan status Covid-19 sebagai pandemi global, yang dalam waktu relatif singkat telah menyebar ke berbagai mancanegara. Covid-19 telah berdampak pada berbagai lini kehidupan seperti ekonomi, sosial-budaya, politik, psikologi, pendidikan, dan sebagainya. Tujuan studi ini ialah untuk memberikan gambaran tentang implikasi pandemi terhadap pendidikan. Studi ini menggunakan metode penelitian kualitatif dengan pendekatan pustaka yang bersumber dari buku-buku, jurnal atau makalah ilmiah, artikel, dan literatur digital lainnya. Studi ini mendeskripsikan bagaimana Covid-19 bisa memepengaruhi dan menata ulang pendidikan baik di berbagai negara-negara dunia termasuk Indonesia. Hasil penelitian menunjukkan ada tiga tren yang muncul dalam dunia pendidikan global di tengah pandemi dan terdapat empat cara Covid-19 bagaimana mengubah cara mendidik bagi generasi yang akan datang. Sehingga, sudah saatnya dunia pendidikan keluar dari status quo dan berbenah diri menuju pendidikan yang futuristik (edukasi 4.0).Kata Kunci: Corona, Pendidikan, Edukasi 4.0